Enhancement of Gluten-Free Cookies Fiber Through Utilization of Spent Coffee Grounds - Anna Abdilla; Sudarminto Setyo Yuwono (Food ScienTech Journal, 2025)
The growing prevalence of gluten intolerance has increased demand for gluten-free food alternatives. This study aimed to enhance the crude fiber content of the gluten-free cookies by incorporating spent coffee ground (SCG) flour and evaluating its effect on physicochemical properties. Cookies were prepared using white rice flour substituted with SCG flour at 10%, 20%, and 30%, and baking powder concentrations of 1%, 2%, and 3%. The cookies were analyzed for crude fiber, moisture content, color (L*, a*, b*, chroma), expansion ratio, porosity, and breaking force. Data were analyzed using a factorial randomized block design, followed by ANOVA, LSD, and DMRT at a 5% significance levell. Results showed that SCG substitution significantly increased crude fiber content, while baking powder concentration also had a significant independent effect. Moisture content increasing with SCG and decreasing with baking powder. Lightness (L*) decreased, while redness (a*), yellowness (b*), and chroma values increased with SCG addition. Expansion ratio was highest at 185%, but decreased with SCG levels above 20%. Porosity decreasing with SCG and increasing with baking powder (p